2019
DOI: 10.1002/adfm.201902017
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Perovskite Light‐Emitting Diodes Using Polycrystalline Core–Shell‐Mimicked Nanograins

Abstract: Making small nanograins in polycrystalline organic-inorganic halide perovskite (OIHP) films is critical to improving the luminescent efficiency in perovskite light-emitting diodes (PeLEDs). 3D polycrystalline OIHPs have fundamental limitations related to exciton binding energy and exciton diffusion length. At the same time, passivating the defects at the grain boundaries is also critical when the grain size becomes smaller. Molecular additives can be incorporated to shield the nanograins to suppress defects at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 57 publications
(71 reference statements)
0
45
0
Order By: Relevance
“… 25 ). Park et al introduced an organic semiconducting additive (2,2ʹ,2″-(1,3,5-benzinetriyl)-tris(1-phenyl-1-H-benzimidazole), TPBi) in the precursor and proposed that a perovskite/organic core–shell structure is formed and accounts for the improvement of the stability 26 . Miao et al introduced benzylamine in the precursor and achieved PeLEDs with a T 50 of 23.7 h at a high current density of 100 mA cm −2 (ref.…”
Section: Introductionmentioning
confidence: 99%
“… 25 ). Park et al introduced an organic semiconducting additive (2,2ʹ,2″-(1,3,5-benzinetriyl)-tris(1-phenyl-1-H-benzimidazole), TPBi) in the precursor and proposed that a perovskite/organic core–shell structure is formed and accounts for the improvement of the stability 26 . Miao et al introduced benzylamine in the precursor and achieved PeLEDs with a T 50 of 23.7 h at a high current density of 100 mA cm −2 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…The fascinating properties of lead halide perovskites such as broad absorption, narrow emission with near unity quantum yield, easier carrier extraction, and high photovoltaic efficiency proffered them as active materials for photovoltaic and light‐emitting applications . Till today, lead halide perovskite is one of the materials which has shown the highest efficiency for light‐emitting diodes (LEDs) and photovoltaic applications . These interesting properties of perovskites are mainly due to their peculiar crystal structures .…”
mentioning
confidence: 99%
“…The additional peaks with wavenumbers in the range of 1250-1500 cm −1 can be ascribed to the fingerprint region of the C=N and C-N bondings of nitrogen heterocyclic rings in the benzimidazole part of TPBi. [22] Moreover, the broad peak at around 3000 cm −1 and the peak at 741.0 cm −1 can be assigned to the vibration of C-H in phenyl ring [23,24] and the C-S bond of TPBi, [24,25] respectively. No significant shifts were observed in these peak positions.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently with this result, other groups demonstrated that TPBi did not chemically react with perovskite when it was used as an additive in the perovskite precursor solutions, which is due to the presence of relatively stronger Lewis bases of DMSO solvent. [22] Figure 3 shows the SEM images of the perovskite thin films with and without the treatments. The pristine perovskite film exhibited an extremely smooth surface with uniform and small grains [Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation